METHODOLOGICAL BASIS FOR FORECASTING THE TAX POTENTIAL OF THE RUSSIAN FEDERATION - Inomjon To‘raevich Jumaniyazov; Aybek Nazarbaevich Abdullaev; Mirza Qilichbayevich Sabirov; Shavkat Bayramovich Babaev (Journals Park Publishing, 2024)
Methodologically, the issues of forecasting tax potential are closely related to issues of its assessment. The system for forecasting the tax potential of the region is the most important indicator of fiscal policy, a form of implementation of the fiscal mechanism.
Keywords: taxes and taxation, taxes, indicators, planning, methods, region, tax potential, cluster, forecasting.